God is back-- pass the plate : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Gibbs, Sandy (Massey University, 2012)
This thesis will consider how video art might critically engage with, and contribute to, a critique of late-capitalism and its relationship with religion within a contemporary art practice. This reflects a shift in my own practice that has become increasingly interested in the complex relationships between institutions and the individual, and the depth at which these are played out in contemporary society. Internationally, many significant cultural theorists and artists1 are actively engaging with what has been dubbed ‘the return of God’ – a rising interest in religion. Drawing a close link with economics, it has been argued that this is a result of the collapse of Communism in the late 1980s and the subsequent global dominance of the American model of capitalism. Paradoxically in New Zealand, our last census shows that we are becoming increasingly secular as a nation.2 During the same period, international neo-liberal free-market reforms were applied to the New Zealand economy, resulting in an extensive amount of corporatisation of institutions. Certain churches reinvented themselves as businesses and entered into a highly competitive but radically shrinking ‘faith’ industry. One of the notable local casualties was the Futuna Chapel and Retreat Centre in Karori, Wellington. Using Futuna Chapel as a specific entry point, this thesis will examine how ideas of economic and religious colonisation have contributed toward the creation of increasingly dislocated and ‘heterotopian’ spaces.3 As a case study, it will elucidate meaningful connections between Futuna Chapel and the housing development built on the site of the demolished retreat centre, in order to set up a dialogic model which closely examines their intersecting relationship.
Keywords: Sandy Gibbs; Criticism and interpretation; Religion in art; Video art